Boron-containing nonwoven polymeric nanofiber mats as neutron shields in compact nuclear fusion reactors - Ozcan, Mucahid; Kam, Erol; Kaya, Cengiz; Kaya, Figen (WILEY, 2022)
Composite materials that contain thermally and chemically stable boron compounds are attractive candidates for applications that require high neutron absorption due to the large neutron absorption cross-section of boron. Electrospun polymer nanofibers have a unique volume-to-surface area, incorporating carbon and hydrogen atoms in their molecular structure that could moderate and thermalize incident neutrons. Nonwoven nanofibers could in turn reduce neutron scattering and increase neutron absorption by providing large surfaces and better atom economy in the shield materials. The expected high absorption will result from improved neutron interaction with high neutron absorbance hydrogen, carbon, and boron atoms in the nanofibers through increased specific surface area and atom economy. In this work, elemental boron-doped PVA polymeric nanofibers are produced for the first time to date for the application of neutron shielding. With the increasing demand for nuclear power generation and radiation therapies in medicine, the need for producing lightweight and flexible materials that could replace the traditional heavy metal/metal carbide-based shields is vital. Similarly, the need for flexible materials that could shield neutrons is also becoming critical for aerospace applications. The effect of boron content on the quality of fibers and neutron shielding capacity is evaluated by using an Am-Be neutron source. Characterization studies of produced nanofibers were carried out by SEM, TGA, FT-IR, and XPS analyses. Results have shown that PVA-based nanofibers doped with wt% 0.1 to 0.5 boron, having fiber diameter distribution between 60 and 330 nm range, could absorb up to 6% of neutron flux.
Keywords: amorphous boron; electrospinning; lightweight composites; neutron absorption; polymer nanofibers; RADIATION; COMPOSITES; NANOPARTICLES; MORPHOLOGY; AGGREGATE; FIBERS; GAMMA; Energy & Fuels; Nuclear Science & Technology